2013
DOI: 10.1007/s11060-013-1048-z
|View full text |Cite
|
Sign up to set email alerts
|

“One week on–one week off”: efficacy and side effects of dose-intensified temozolomide chemotherapy: experiences of a single center

Abstract: To evaluate in a single center retrospectively the efficacy and tolerability of a weekly regimen, which alternates temozolomide (TMZ) in patients with recurrent or progressive high-grade glioma (HGG). From January 2005 until June 2011, 54 patients with recurrent or progressive HGG were treated with TMZ 150 mg/m²/day on days 1-7 and 15-21 of a 28-day cycle ("one week on-one week off" scheme; TMZ 7/14) with individual dose adjustment depending on toxicity. The majority of patients (n = 48, 89 %) was treated at f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Recently, a Phase II clinical trial reported that TMZ dose-dense regimen treated rMG with a certain efficacy. 12 However, TMZ dose-dense regimen was not effective for case 1 in this report.…”
Section: Discussionmentioning
confidence: 52%
“…Recently, a Phase II clinical trial reported that TMZ dose-dense regimen treated rMG with a certain efficacy. 12 However, TMZ dose-dense regimen was not effective for case 1 in this report.…”
Section: Discussionmentioning
confidence: 52%
“…48,49 The benefit of MGMT gene silencing in patients with glioma undergoing chemotherapy with TMZ is well elucidated. 26 Efforts to deplete MGMT activity to increase the cytotoxic potential of alkylating agents led to exploration of metronomic TMZ schedules in patients with glioma 26,50,51 with the goal of improving antitumor activity and overcoming resistance. [52][53][54][55] Several regimens consisting of MS TMZ in both newly diagnosed and recurrent gliomas as well as in melanoma have been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Multifocal glioblastoma is defined as intracranial GBM with multiple synchronous foci, and there is a known anatomical route for spread of diseases between lesions. It only consists of a small part of glioblastoma, with an incidence of 0.5% to 20% [ 7 , 10 , 11 ]. Thomas et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 29 ] mentioned that temozolomide treatment was continued for more than 6 cycles by 80.5% of neuro-oncologists in Spain. There are many kinds of long-term usage of temozolomide nowadays, three distinctive regimens are standard ‘5/28’ protocol (150 to 200 mg/m 2 on days 1 to 5 every 28 days) [ 6 ], ‘1 week on-1 week off’ protocol (150 mg/m 2 on days 1 to 7 and 15 to 21 of a 28-day cycle) [ 7 ], and dose-dense protocol (75 to 100 mg/m 2 on days 1 to 21 every 28 days) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%